Odpowiedzi

2010-01-11T19:07:58+01:00
Y-2x=1/*2
y+4x=13
2y-4x=2
y+4x=13
3y=15
y=5
5 -2x=1
y=5
-2x=-4
y=5
x=2

2.
5y-x=3
y+x=3
6y=6
y=1
5- x=3
x=2
  • Użytkownik Zadane
2010-01-11T19:08:50+01:00
B) y=2x+1
4x+y=13

y-2x=1/×2
y+4x=13

2y-4x=2
y+4x=13
-----------------
3y=15/:3
y=5

2x=y-1
2x=5-1
2x=4/:2
x=2
y=5

C) 5y-x=3
x=3-y

5y-x=3
y+x=3
---------------
6y=6/:6
y=1

x=3-y
x=3-1
x=2
y=1
Najlepsza Odpowiedź!
2010-01-11T19:09:16+01:00
B) y=2x+1
4x+y=13

y=2x+1
4x+2x+1=13

y=2x+1
4x+2x+1=13

y=2x+1
6x+1=13

y=2x+1
6x=13-1

y=2x+1
6x=12/:6

y=2x+1
x=2

y=2*2+1
x=2

y=4+1
x=2

y=5
x=2

c) 5y-x=3
x=3-y

5y-3-y=3
x=3-y

6y-3=3
x=3-y

6y=3+3
x=3-y

6y=6/:6
x=3-y

y=1
x=3-1

y=1
x=2

to jest dobrze na pewno ,bo miałam na zeszłej lekcji to zadanie xD
2 5 2